Intravenous vitamin K1 normalises prothrombin time in 1 hour in dogs with anticoagulant rodenticide toxicosis. Issue 6 (18th March 2020) - Mooney, ET; Agostini, G; Griebsch, C; Hickey, M
Abstract : Four dogs with anticoagulant rodenticide toxicosis were treated with intravenous vitamin K1 in lieu of plasma transfusion due to client cost constraints. Two dogs experienced a suspected anaphylactoid reaction, necessitating cessation of the treatment in one dog. Prothrombin time was rechecked 1 h after treatment in the remaining three dogs and all results were within the normal reference range. All four dogs were discharged from hospital within 48 h of presentation. Intravenous vitamin K1 rapidly reverses the coagulopathic state in dogs with anticoagulant rodenticide toxicosis. It is a viable alternative therapy to plasma transfusion if circumstances preclude its use; however, patients must be monitored for anaphylactoid reactions.